Процесні підходи до аудиту систем менеджменту інформаційної безпеки - Євсюкова, О. О. (ХНУРЕ, 2023)
Information security covers the tools and processes that organizations use to protect information. This includes policy settings that prevent unauthorized people from accessing business or personal information. Information system security services audit deal with the identification and analysis of potential risks, their mitigation or removal, with the aim of maintaining the functioning of the information system and the organization's overall business. While expanding online, cyber risks also increased with more targeted attacks against organizations ranging from small to large. Performing a security audit can help organizations by providing information related to the risks associated with their networks. It can also help in finding security loopholes and potential vulnerabilities in their system. Thereby patching them on time and keeping hackers at bay